1983
DOI: 10.1016/s0022-5347(17)52256-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcoma of the Penis: Case Report and Review of the Literature

Abstract: We report a case of fibrosarcoma of the penis and review the literature. We believe that amputation is the most effective therapy and the role of lymphadenectomy is equivocal. All cases should be reported to better define the roles of various oncologic modalities of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For this review of the literature, we identified 137 case reports with 269 total cases of hyperparathyroidism in pregnancy with the earliest case report published in 1947. There were 85 cases with a single report and 32 case series with the numbers of cases reported varying from 2 to 28 patients in each case report 1,3,5,10–143 …”
Section: Etiology Prevalence and Backgroundmentioning
confidence: 99%
“…For this review of the literature, we identified 137 case reports with 269 total cases of hyperparathyroidism in pregnancy with the earliest case report published in 1947. There were 85 cases with a single report and 32 case series with the numbers of cases reported varying from 2 to 28 patients in each case report 1,3,5,10–143 …”
Section: Etiology Prevalence and Backgroundmentioning
confidence: 99%
“…142 Other sarcomas of the penis are rare, but there have been reported cases of angiosarcomas, 144,145 epithelioid hemangioendotheliomas, 146,147 epithelioid sarcomas, 148,149 leiomyosarcomas, 150 undifferentiated pleomorphic sarcomas, 151,152 malignant schwannomas, 153,154 rhabdomyosarcomas, [155][156][157][158] and fibrosarcomas. [159][160][161]…”
Section: Basal Cell Carcinomamentioning
confidence: 99%